Temporomandibular disorders among adult patients: Relationship with personality traits and other factors - Hassan Adnan Alshawaf; Mohammed Ali Alnemer; Majid Alawi Alsafwani; Faisal Abdulmonem Alhalal; Moayad Mohammed Aljeshi; Muhammad Ashraf Nazir (PLoS ONE, 2026)
Introduction Temporomandibular disorders (TMDs) refer to the pain and dysfunction of the temporomandibular joints and associated masticatory muscles. There is a lack of evidence about the relationship between TMDs and personality traits. The aim of the study was to evaluate temporo-mandibular disorders and their relationship with personality traits and other study variables among adult patients in Dammam, Saudi Arabia. Methods This cross-sectional study was conducted at the Dental Hospital of the College of Dentistry, Imam Abdulrahman Bin Faisal University (IAU), Dammam, Saudi Arabia. Adult male and female patients attending dental hospital who provided written consent were included in the study. A self-administered questionnaire was administered among participants, which included demographic information, Big-Five Inventory-2 Short form (BFI-2 S) for personality traits, and Fonseca’s questionnaire for temporo-mandibular disorders (TMDs). A t-test, one-way ANOVA test, and multiple linear regression analysis were performed in the study. Results The study included 500 participants, with 66.4% males and 33.6% females. Most participants (59.2%) had TMDs, with 40% mild TMDs, 14.6% moderate TMDs, and 4.6% severe TMDs. Females demonstrated a significantly higher mean score of Fonseca’s questionnaire (31.79 ± 21.96) compared to males (22.32 ± 18.75) (P < 0.001). The participants with no education had the highest mean score of Fonseca’s questionnaire (52.50 ± 33.06) compared to those with school education (27.09 ± 18.96) and college/university education (23.49 ± 19.78) (P < 0.001). The participants with arthritis and sleep disorders demonstrated significantly greater severity of TMDs than those without these conditions (P < 0.001). There was a significant negative correlation between TMDs and agreeableness (r = −0.26, P < 0.001) and conscientiousness (r = −0.23, P < 0.001). However, a significant positive correlation (r = 0.33, P < 0.001) can be observed between TMDs and neuroticism. According to multiple linear regression analysis models, agreeableness (B = −1.17, P < 0.001), conscientiousness (B = −1.04, P < 0.001), and neuroticism (B = 1.45, P < 0.001) remained statistically significant predictors of TMDs after controlling for age, gender, nationality, education, and monthly income. Conclusion The study found that TMDs were highly prevalent among adult patients. TMDs were significantly related to female gender and low education level. The participants with arthritis and sleep disorders demonstrated significantly increased severity of TMDs. Neuroticism was significantly correlated with the severity of TMDs. On the other hand, agreeableness and conscientiousness were negatively correlated with TMDs and emerged as protective predictors against TMDs. Adult patients should be screened for TMDs and personality traits, and multidisciplinary treatment plans involving treatments for TMDs and psychological support should be tailored for them.